Pengaruh Self Reward terhadap Motivasi Belajar Mahasiswa PGSD Universitas Negeri Padang (Jurnal Arjuna : Publikasi Ilmu Pendidikan, Bahasa dan Matematika, 2025)
This study aims to explore the influence of self-reward on the learning motivation of PGSD (Primary School Teacher Education) students at Universitas Negeri Padang. Self-reward refers to a form of self-appreciation given by individuals after achieving specific goals or completing tasks. This research employed a qualitative approach through interviews and observations involving several students. The pre-test results indicated that most students had a moderate level of learning motivation, with an average score of 65 out of 100. After implementing self-reward strategies such as buying food, playing games, going to karaoke, and taking class trips students demonstrated increased motivation, with the post-test average score rising to 78. Students reported feeling more enthusiastic, confident, and consistent in engaging with academic activities after practicing self-reward. Additionally, self-reward served as an effective coping mechanism to combat academic fatigue and boredom. In conclusion, self-reward plays a significant role in enhancing students’ learning motivation and can be considered a recommended personal development strategy in higher education settings.